2017
DOI: 10.1002/jcp.26058
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenic commitment and differentiation of human mesenchymal stem cells by low‐intensity pulsed ultrasound stimulation

Abstract: Low-intensity pulsed ultrasound (LIPUS) as an adjuvant therapy in in vitro and in vivo bone engineering has proven to be extremely useful. The present study aimed at investigating the effect of 30 mW/cm LIPUS stimulation on commercially available human mesenchymal stem cells (hMSCs) cultured in basal or osteogenic medium at different experimental time points (7, 14, 21 days). The hypothesis was that LIPUS would improve the osteogenic differentiation of hMSC and guarantying the maintenance of osteogenic committ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 62 publications
2
40
0
Order By: Relevance
“…An interesting point in question was to determine the role of the miR-33a family in pre-osteoblast cells in order to identify a timeline of miR-33a-3p and miR-33a-5p expression during hMSCs osteoblast commitment. For this reason, we obtained pre-osteoblast cells by maintaining hMSCs in osteoblast medium [45], and a significant difference on miR-33a-3p and 5p expression patterns was evidenced ( Figure 4A). Surprisingly, the inhibition of miR-33a-5p on hMSCs maintenance in osteogenic medium induced an increase of miR-33a-3p expression, suggesting possible activation of a cell control mechanism from hMSCs to maintain a balance of miRNAs expression during the osteoblast differentiation process ( Figure 4B).…”
Section: Discussionmentioning
confidence: 99%
“…An interesting point in question was to determine the role of the miR-33a family in pre-osteoblast cells in order to identify a timeline of miR-33a-3p and miR-33a-5p expression during hMSCs osteoblast commitment. For this reason, we obtained pre-osteoblast cells by maintaining hMSCs in osteoblast medium [45], and a significant difference on miR-33a-3p and 5p expression patterns was evidenced ( Figure 4A). Surprisingly, the inhibition of miR-33a-5p on hMSCs maintenance in osteogenic medium induced an increase of miR-33a-3p expression, suggesting possible activation of a cell control mechanism from hMSCs to maintain a balance of miRNAs expression during the osteoblast differentiation process ( Figure 4B).…”
Section: Discussionmentioning
confidence: 99%
“…LIPUS-stimulated MSC show an increase in hydroxyapatite content and in the release of type I collagen and osteopontin, and this seems to be additive to the use of osteogenic differentiation medium [ 45 ]. Human nucleus pulposus cells are a promising cell therapy source for intervertebral disc degeneration, and LIPUS promotes the production of type II collagen, aggrecan, and Sox9 in these cells in vitro.…”
Section: Biological Effects Of Ultrasoundmentioning
confidence: 99%
“…The results demonstrated that 10 ppm Ti ions could restrict the extension of osteoblast pseudopodia and inhibit cell spreading. osteoblast differentiation covers osteogenic commitment and osteogenic differentiation (45). during the osteogenic commitment process, runx2 is considered to be one of the core transcription factors (46), whilst alP and OSX are considered to be specific markers for the osteogenic differentiation process (47,48).…”
Section: Discussionmentioning
confidence: 99%